Étude de certains aspects du droit nucléaire canadien - Jobin, Jean-François (Les Cahiers de droit, 1981)
The law respecting nuclear energy has to date been the subject of relatively few studies in Canada. Considering, however, the growing importance of nuclear energy as a new or additional form of energy, besides oil, gas, coal and hydroelectric power, and on the other hand, the increase in public concern about the possible consequences of the nuclear option, especially on health and the environment, this area of law is undoubtedly bound to experience a major development. The purpose of the present article is to study existing federal legislation on the matter, as well as its effects on certain provincial jurisdictions, more particularly in Quebec. The author, after recalling certain technical data concerning components and functions of nuclear reactors, proceeds to analyse the main intervenors in the nuclear field, as contemplated by the Atomic Energy Control Act. One cannot help but acknowledge that the Atomic Energy Control Board, by means of its important supervisory and regulatory powers, intervenes at all stages of the nuclear cycle. The author also studies the constitutional basis for the federal intervention in this field of activity. After eliminating the national defence power, the national dimension theory and the emergency power as possible alternatives, he concludes that while Parliament may perhaps invoke its residuary power, its declaratory power appears as the surest constitutional basis for asserting its legislative authority over that particular matter. In the last part of the article, the author attempts to emphasize the effects of federal intervention on provincial property rights over uranium mines, and on provincial jurisdictions over labour relations, health and safety at the workplace and environmental protection. This analysis points out that provincial legislative authority over the management and development of their natural resources is not only inapplicable in respect of uranium, but that their property rights over uranium mines are rather precarious. It seems clear, further, that jurisdiction over labour relations within nuclear undertakings lies exclusively with the federal authority. One could argue that such is also the case with those aspects of nuclear undertakings which are connected with workers' health and safety as well as environmental protection, since those matters are intimately linked with the control of atomic energy. Two main conclusions can be drawn from this study. Firstly, it appears certain that Parliament, in legislating as it did, intended to regulate the whole nuclear energy cycle, from the extraction of uranium ore to the ultimate disposal of nuclear waste. Secondly, that authority could hardly be challenged by provinces or any other interested party, at least on constitutional grounds.